DEVELOPMENTS OF DIGESTIVE TRACT IN LARVAE OF CLIMBING PERCH, Anabas testudineus (Bloch) - Yulintine Yulintine; Enang Harris; Dedi Jusadi; Ridwan Affandi; Alimuddin Alimuddin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
Climbing perch, Anabas testudineus (Bloch) is a potential species for aquaculture in Kalimantan, Indonesia and belongs to Anabantidae family. The development of its digestive tract was evaluated on larvae reared under culture conditions of 28oC-30oC, from hatching to 30 days after hatching using histological and morphological methods. The larvae were kept in six 100-L tanks. They were fed with rotifers and microalgae from day 2nd after hatching to day 10th; Artemia nauplii from day 7th to day 15th; Artemia meta-nauplii from day 15th to day 20th; and Tubifex worm from day 20th onwards. The development of digestive tract in climbing perch followed the general pattern described for other species. Shortly after hatching, its digestive system was found to be consisted of an undifferentiated straight tube laying dorsally to the yolk sac. At first feeding (day 2nd), both mouth and anus had opened and the yolk sac was partially absorbed. On day 3, the digestive tract was fully differentiated into buccopharynx, esophagus, intestine and rectum. The two pyloric caeca appeared on day 25th after hatching, indicating the transition from larval to juvenile stage and acquisition of an adult type of digestion.